Fundamentos para uma proposta de musealização da Capela de Nª Sª das Mercês do Palácio do Marquês de Pombal em Oeiras - Monereo, Carla Mariza Batalha Garcia, 1967- (2014)
This dissertation Museography in Museology and aims to contribute as a basis for a pro- posed musealization Chapel of Oeiras sumptuous palace of the Marquis of Pombal, Conde de Oeiras, a place of worship, which we see as a big container values, customs, people and traditions. Elements, all assets essential to the achievement of the project defended. In the opinion of the acquis architectural, artistic and historical, the palace is closely related to the work of Sebastião José Carvalho e Melo , Minister of D. José. This research results from personal taste by the palace chapel of Oeiras , in particular the decorative arts , the clear interest in developing new initiatives for the dissemination of the artistic heritage and apply the knowledge acquired in the Master in Museology and Museo- graphy. This is a case study which analyzes in situ the work assigned by Italian artist Giovanni Gros- si, taking into account their integration in spaces stucco wall of the chapel, established as a strategy , the study of the characteristics of their work. Consider the scientific studies on the art of stucco work, within the decorative arts and buildings that have compared the orna- mental plaster and decorative function in its interior, whose authorship has been attributed to the plasterer. We identify the technical craft of estucaria, modes and limits of its use in the Rococo period , during which it was widespread. Based on the analytical study of the set of decorative plasters, equate its meaning and pur- pose, we present solutions that enable a program and museological museum, aiming to safe- guard the preservation of cultural heritage and the creation of an educational tool around the Heritage Education and has audience as the sighted and the blind. In the proposed museali- zation beyond the relations of ownership and enjoyment that are established with different audiences we seek to contribute to the reduction of social exclusion and access for people with visual impairments to museums